2018
DOI: 10.21776/ub.rjls.2018.005.03.6
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological in Gills, Hepatopancreas and Gut of White Shrimp (Litopenaeus Vannamei) Infected White Feces Disease (WFD)

Abstract: White feces disease which is the presence of white feces floating on the surface of the water. Physical disruption of white feces disease attacked by exocytes becoming soft. the cause of white feces disease (WFD) is a decrease in environmental quality such as salinity, dissolved oxygen and ammonia. White feces disease is associated with gregarine protozoa in the Apicomplexa phylum. Gregarine parasitic infection from the type of nematopsis that was interacted with Vibrio and Vibrio bacteria found in white shrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…This implies a resilience of bacterial communities in shrimp pond water after short disturbances, as can also be observed in other environments 49 , 59 , 60 . However, we point out that prolonged exposure to water deterioration and elevated pathogen proportions may increase disease severity and lead to mass mortality of cultured shrimps as previously observed 5 , 61 . Our findings on the application of commercial probiotics to cure WFD in shrimps revealed that probiotic bacteria such as Lactobacillus were absent in WB, IB and FSB, suggesting that such an application was not effective.…”
Section: Discussionsupporting
confidence: 65%
“…This implies a resilience of bacterial communities in shrimp pond water after short disturbances, as can also be observed in other environments 49 , 59 , 60 . However, we point out that prolonged exposure to water deterioration and elevated pathogen proportions may increase disease severity and lead to mass mortality of cultured shrimps as previously observed 5 , 61 . Our findings on the application of commercial probiotics to cure WFD in shrimps revealed that probiotic bacteria such as Lactobacillus were absent in WB, IB and FSB, suggesting that such an application was not effective.…”
Section: Discussionsupporting
confidence: 65%
“…Even when they do, the WFS is not associated with severe mortality or other serious production problems (Sanguanrut et al, 2018). In our experience, white midguts may also be caused by heavy gregarine infections, severe Vibrio infections and hemocytic enteritis caused by ingested blue-green algae (Anjaini et al, 2018;Somboon et al, 2012), but they are not usually associated with accumulation of floating fecal mats.…”
Section: Introductionmentioning
confidence: 59%
“…The White Feces Disease (WFD) is the most common disease found in the Pacific white shrimp. An early indication of this disease is the white dirt floating on the water surface [9]. Histology samples of hepatopancreas from the Pacific white shrimp showing White Feces Disease (WFD) symptoms were collected from two ponds.…”
Section: Discussionmentioning
confidence: 99%